"Not‐so‐popular" orthogonal pairs in genetic code expansion. (19th January 2023) - Andrews, Joseph; Gan, Qinglei; Fan, Chenguang
Abstract: During the past decade, genetic code expansion has been proved to be a powerful tool for protein studies and engineering. As the key part, a series of orthogonal pairs have been developed to site‐specifically incorporate hundreds of noncanonical amino acids (ncAAs) into proteins by using bacteria, yeast, mammalian cells, animals, or plants as hosts. Among them, the pair of tyrosyl‐tRNA synthetase/tRNA Tyr from Methanococcus jannaschii and the pair of pyrrolysyl‐tRNA synthetase/tRNA Pyl from Methanosarcina species are the most popular ones. Recently, other "not‐so‐popular" orthogonal pairs have started to attract attentions, because they can provide more choices of ncAA candidates and are necessary for simultaneous incorporation of multiple ncAAs into a single protein. Here, we summarize the development and applications of those "not‐so‐popular" orthogonal pairs, providing guidance for studying and engineering proteins.